Epicatechin Isolated from Litchi chinensis Sonn. (Litchi) Fruit Peel Ethyl Acetate Extract Modulated Glucose Uptake in Chang Cells and Suppressed ROS Production in RAW 264.7 Macrophages - Gloria O. Izu; Nomonde P. Mapasa; Jennifer Nambooze; Maria S. Chukwuma; Emmanuel Mfotie Njoya; Gaetan T. Tabakam; Susanna L. Bonnet; Tshepiso J. Makhafola; Samson S. Mashele; Chika I. Chukwuma (MDPI AG, 2024)
Bioactive flavonoid epicatechin has been reported in the peel of litchi fruit but isolated from its hydroalcoholic extracts. This study isolated epicatechin with cellular glucose uptake modulatory and ROS production inhibitory properties from the ethyl acetate (EtOAc) extract using a bioassay-guided approach. The fruit peel was defatted with hexane and sequentially extracted using dichloromethane (DCM), EtOAc, methanol (MeOH) and water. In vitro phytochemical models, namely antioxidant (Fe3+ reducing, radical scavenging and anti-linoleic acid peroxidative) and glycaemic control (α-glucosidase and α-amylase inhibitory and glucose uptake modulatory), were employed for the bioassay-guided isolation, while the isolated compound was characterised using NMR and mass spectrometry and assessed for dose-dependent inhibition of α-glucosidase and lipopolysaccharide (LPS)-induced cellular ROS production, as well as modulation of cellular glucose uptake. Relative to the other extracts, the EtOAc extract had appreciable phenol and flavonoid contents, which perhaps influenced its potent anti-lipid peroxidative (65.0%) and α-glucosidase inhibitory (52.4%) effects. The α-glucosidase inhibitory potency of the fractions (1-8) from the EtOAc extracts correlated with their flavonoid contents, with fraction 5 outperforming other fractions. The fraction comprised a pool of fractions obtained from the DCM:MeOH:water (7:3:0.281 v/v/v) solvent system. LC-MS revealed the predominant presence of epicatechin in fraction 5, which was later isolated from one of the sub-fractions (sub-fraction 4) of fraction 5. This sub-fraction had stronger anti-lipid peroxidative (65.5%), α-glucosidase inhibitory (65.8%) and glucose uptake modulatory (38.2%) effects than the other sub-fractions from fraction 5, which could have been influenced by the isolated epicatechin. Moreover, the isolated epicatechin inhibited α-glucosidase (IC50 = 35.3 µM), modulated cellular glucose uptake (EC50 = 78.5 µM) and inhibited LPS-induced ROS production in RAW 264.7 macrophages in a dose-dependent fashion [IC50 = 18.9 µM; statistically comparable (p > 0.05) to ascorbic acid, IC50 = 9.57 µM]. Epicatechin from litchi peel EtOAc extract could potentiate glucose uptake modulatory, α-glucosidase inhibitory and ROS suppressive capacities, which could be influential in the use of litchi fruit peel for managing diabetes and associated oxidative damage.